2020
DOI: 10.1038/s41419-020-03262-7
|View full text |Cite
|
Sign up to set email alerts
|

Human iNSC-derived brain organoid model of lysosomal storage disorder in Niemann–Pick disease type C

Abstract: Recent studies on developing three-dimensional (3D) brain organoids from stem cells have allowed the generation of in vitro models of neural disease and have enabled the screening of drugs because these organoids mimic the complexity of neural tissue. Niemann-Pick disease, type C (NPC) is a neurodegenerative lysosomal storage disorder caused by mutations in the NPC1 or NPC2. The pathological features underlying NPC are characterized by the abnormal accumulation of cholesterol in acidic compartments, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…However, there was no difference in the level of the immature neuron marker TUJ1. Finally, to estimate the neural level in the 3D brain organoid model, we followed the 3D culture protocol as described in the Methods section for 28 days [ 26 ]. Immunostaining analysis showed that the number of neural progenitor markers was similar in WT and PSEN KO organoids, but the neuronal level was markedly reduced in PSEN KO organoids (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no difference in the level of the immature neuron marker TUJ1. Finally, to estimate the neural level in the 3D brain organoid model, we followed the 3D culture protocol as described in the Methods section for 28 days [ 26 ]. Immunostaining analysis showed that the number of neural progenitor markers was similar in WT and PSEN KO organoids, but the neuronal level was markedly reduced in PSEN KO organoids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the effects of APP-CTFs accumulation on mitophagy in Alzheimer’s disease were related to PSEN mutation, we generated induced neural stem cells (iNSCs) from fAD patient-derived fibroblasts, as described in our previous study [ 25 , 26 ]. Because terminally differentiated neurons derived from the iNSC lineage are very useful for understanding the pathophysiological mechanisms of many neurodegenerative diseases [ 27 ], we generated AD patient-iNSCs to study the pathological mechanism of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed how healthy organoids can be used in the assessment of drug toxicity such as cardiotoxicity (Eder et al, 2016), nephrotoxicity (Takasato et al, 2015), and hepatotoxicity (Kostadinova et al, 2013;Katsuda et al, 2017). On the other hand, organoids are used to study the effect of some drugs on preexisting diseases, such as primary tumors (Jabs et al, 2017;Abbasi, 2018;Vlachogiannis et al, 2018), rare genetic diseases including cystic fibrosis (Fleischer et al, 2020), neurological diseases (Lee S. E. et al, 2020;Costamagna et al, 2021), and infectious diseases (Zhou et al, 2017;Heo et al, 2018). Other studies reported the use of cancer organoid lines, for example colorectal cancer (CRC) organoid lines to screen 83 drugs (van de Wetering et al, 2015), breast cancer organoid lines for testing inhibitors human epidermal growth factor receptor (HER) signaling pathway (Reid et al, 2018), or bladder cancer organoid lines for testing 26 drugs (Lee et al, 2018).…”
Section: Organoids In Drug Screeningmentioning
confidence: 99%
“…Many researchers have employed brain organoids derived from human induced pluripotent stem cells (hiPSCs) to better understand human neural development and detailed pathology related to many neurodegenerative diseases [ 34 36 ]. Brain organoids resemble features of various brain regions and provide an opportunity to study brain development and understand detailed mechanisms of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%